The costs of achieving the millennium development goals through adopting organic agriculture - Anil Markandya; Sununtar Setboonsarng; Qiao Yu Hui; Rachanee Songkranok; Adam Stefan (Asian Development Bank Institute (ADBI), 2010)
This paper provides estimates of the costs of organic agriculture (OA) programs, and sets them in the context of the costs of attaining the United Nations' Millennium Development Goals (MDGs). It analyzes the costs of OA programs in four case studies: Wanzai, PRC; Wuyuan, PRC; Kandy, Sri Lanka; and Ubon Ratchathani, Thailand. The results show considerable variation across the case studies, suggesting that there is no clear structure to the costs of adopting OA. Costs do depend on the efficiency with which the OA adoption programs are run. The lowest cost programs were more than ten times less expensive than the highest cost ones. A further analysis of the gains resulting from OA adoption reveals that the costs per person taken out of poverty was much lower than the World Bank's estimates, based on income growth in general or based on the detailed costs of meeting some of the more quantifiable MDGs (e.g., education, health, and environment).
Keywords: Q01; Q18; Q56; 330; Millennium Development Goals; Ökologischer Landbau; Soziale Kosten; China; Sri Lanka; Thailand